KONSEP PENERAPAN PIDANA MATI TERHADAP TINDAK PIDANA KORUPSI YANG DILAKUKAN PADA KEADAAN BENCANA DALAM PERSPEKTIF HAK ASASI MANUSIA - Rachmanto, Fandri (Fakultas Hukum Universitas Narotama, 2025)
The application of the death penalty for corruption in disaster situations has raised pros and cons in various parts of the world. From a human rights perspective, the application of the death penalty is considered a violation of human rights because it violates the right to life. Human rights state that every individual has the right to life and should not be given the death penalty for any crime. In addition, the application of the death penalty is also considered to violate the right to protection from inhumane and insulting treatment of human dignity. This is because the process of executing the death penalty often involves inhumane and painful treatment for prisoners. The implementation of the death penalty for corruption is also considered an effective form of punishment to eradicate corruption in disaster situations. Corruption in disaster situations will result in injustice and suffering for many individuals who are victims of the disaster. Therefore, the application of the death penalty is considered a strong signal to perpetrators of corruption that their actions will not be tolerated and will be given a punishment commensurate with the losses they cause.